Method reverse encoding structural gravimetric numbers for decline bit rate video stream - Бараннік, Володимир Вікторович; Красноруцький, Андрій Олександрович (Ukrainian Information Security Research Journal, 2013)
Presently practically all technology of video information services grant do with the preliminary decline of video-stream speed. For this purpose technologies of images compression are integrated in the info-communication systems. The existent compression degrees at video pictures possible quality do not provide the required bit speeds. A problem, conditioned the insufficient carrying capacity of tele-communication networks, and its lag from constantly growing’s intensities of video traffic, shows up as a result. As a result necessary bit speed is arrived at due to the loss of video information resource integrity. Modernization of network physical basis presents by itself difficult structurally technical process, and requires enormous investments and time. Therefore overcoming of the folded disbalance between bit speed and carrying capacity of network conducted on the basis of images compression technology perfection. In the article examined the stages of creation of the modified position coding of binary elements, being based on forming of code (since junior elements and realization of cross order of accordance between the number elements and by the elements of series lengths array column). A ground is conducted: exceptions of out-of-control losses of information about the binary objects of transforms binary description; reductions of service information content; declines of operations amount for technology coding realization. In the article developed recurrent reversible even coding of the extended position structural-weight numbers of variable length, being based on the rule of elements selection for number expansion.